Outcomes of Menstrual Management Use in Transgender and Gender-Diverse Adolescents. Issue 4 (9th April 2023) - Schwartz, Beth I.; Bear, Benjamin; Short, Vanessa L.; Kazak, Anne E.
Abstract : Among gender-diverse patients who used medical menstrual management, we found improved bleeding, pain, dysphoria, and moods related to menstruation and high continuation and amenorrhea rates. Abstract : OBJECTIVE: To describe and compare the outcomes of various menstrual-management methods, including method choice, continuation, bleeding patterns, amenorrhea rates, effect on moods and dysphoria, and side effects, in transgender and gender-diverse adolescents. METHODS: This was a retrospective chart review of all patients seen in a multidisciplinary pediatric gender program from March 2015 to December 2020 who were assigned female at birth, had achieved menarche, and used a menstrual-management method during the study period. Data were abstracted on patient demographics and menstrual-management method continuation, bleeding patterns, side effects, and satisfaction at 3 months (T1) and 1 year (T2). Outcomes were compared between method subgroups. RESULTS: Among the 101 included patients, 90% chose either oral norethindrone acetate or a 52-mg levonorgestrel (LNG) intrauterine device (IUD). There were no differences in continuation rates for these methods at either follow-up time. Almost all patients had improved bleeding at T2 (96% for norethindrone acetate and 100% for IUD users), with no difference between subgroups. Amenorrhea rates were 84% for norethindrone acetate and 67% for IUD at T1 and 97% and 89%, respectively, at T2, with no differences at either point. The majority of patients had improved pain, menstrually related moods, and menstrually related dysphoria at both follow-up points. There were no differences in side effects between subgroups. There were no differences in method satisfaction between the groups at T2. CONCLUSION: Most patients chose norethindrone acetate or an LNG IUD for menstrual management. Continuation, amenorrhea, and improved bleeding, pain, and menstrually related moods and dysphoria were high for all patients, indicating that menstrual management is a viable intervention for gender-diverse patients who experience increased dysphoria related to menses.